Self Efficacy Description of Family Members Who Experience Stigma While Caring for People with Odgj in Buduran District, Sidoarjo - Qualitative Research - Fara Farina; Ah Yusuf; Sylvia Dwi Wahyuni (Psychiatry Nursing Journal (Jurnal Keperawatan Jiwa), 2020)
Introduction: The stigma that people with ODGJ get from society is also felt by their families, they will feel sad, ashamed, afraid, and feel that they are not free to do manyÂ outside activities. The psychological burden felt by the caring family can affect the adequacy of self-efficacy in carrying out daily activities. The purpose of this study is to describe the self-efficacy of families experiencing stigma while caring for people with disorders in Buduran District, Sidoarjo.Method: This type of research design used is a phenomenological method with 15 participants who have family members with ODGJ through purposive sampling technique. The data collection technique used was in-depth interview. The data were analyzed using the Colaizi technique.Results: This study resulted in several themes, namely, 1) community stigma, 2) perception of family members, 3) treatment received by family members, 4) selfacceptance of family members, 5) social support, 6) coping mechanisms, 7) patient health conditions, and 8) mental strength of family members. The self-efficacy picture of family members caring for ODGJ sufferers is based on the perceived problem magnitude in the form of community stigma on the magnitude dimension, so that adaptive or maladaptive coping mechanisms are formed on the strength dimension, resulting in a fairly limited range of behavior on the generality dimension, and expectations of family members healing of sufferers and meaning of conditions. This condition can affect the self-efficacy picture of family members who care for people with ODGJ.Conclusion: a family whose relatives as ODGJ sufferers are prone to inadequate selfefficacy due to the patient's abnormal behavior. The family stigma that develops is also felt by the family and becomes a psychological burden.